An initiative to link between research and support for young farmers who access the sub-measure 6.1 - RDP 2014-2020 - Ana Ursu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The paper highlights the involvement of field research in achieving a model farm calves for fattening and associated with basic fodder popularizing information and for practical use, which is necessary for young farmers first install the head / manager of a holding in a production animal competitive. This study is based on a business plan prepared according to the Applicant's Guide for sub-measure 6.1 of the RDP 2014-2020, and meetings with young farmers. Development of a forage-based livestock farms related constitutes an advantage for farmers resulting from the combination of two types of activities in that young farmer could sell his crop production on the farm, thus reducing cost production of animal products by 60%. In the same time, the young farmer can judiciously organize his activities in both farms livestock and crops plant having a rigorous and permanent control, so that it can intervene if there are any financial losses during the production process. The results reveal that young farmers could benefit from improved access to information, but there is no real benefit assessment because of the small number of relevant surveys.
Keywords: 330; research; model; farm; sub; young farmer